1983
DOI: 10.1203/00006450-198304000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Defective Monocyte Chemotaxis in Children with Down's Syndrome

Abstract: SummaryUnder-agarose random migration, chemokinesis and chemotaxis of monocytes from 36 patients with Down's syndrome were compared to those of monocytes from 42 healthy, age-matched control children. Random migration of monocytes from patients with Down's syndrome was comparable to that of controls. In contrast, chemotaxis of monocytes from patients with Down's syndrome was significantly decreased (P < 0.001) when com~ared to that of controis, even though chemokinesis was significantly increased (P < 0.001). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 12 publications
0
8
0
4
Order By: Relevance
“…Aproximadamente 10% dos pacientes atendidos apresentavam Síndrome de Down, a qual está relacionada com limitações no desenvolvimento físico e mental, e com deficiência imunológica 16,17 . Esta última, associada à má higiene bucal que esses indivíduos Indivíduos com alterações neurológicas geralmente apresentam redução do fluxo e do pH salivares, em virtude da utilização sistemática de medicamentos, como os anticonvulsivantes, antipsicóticos, ansiolíticos, antiepilépticos e antidepressivos 19 .…”
Section: Discussionunclassified
“…Aproximadamente 10% dos pacientes atendidos apresentavam Síndrome de Down, a qual está relacionada com limitações no desenvolvimento físico e mental, e com deficiência imunológica 16,17 . Esta última, associada à má higiene bucal que esses indivíduos Indivíduos com alterações neurológicas geralmente apresentam redução do fluxo e do pH salivares, em virtude da utilização sistemática de medicamentos, como os anticonvulsivantes, antipsicóticos, ansiolíticos, antiepilépticos e antidepressivos 19 .…”
Section: Discussionunclassified
“…In DS, susceptibility to infection is increased as a result of both specific and non-specific abnormalities of the immune system [3][4][5][6][7][8]. It has also been demonstrated that in DS patients, the prevalence and severity of advanced periodontal disease are increased [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Included are deficiencies in adaptive immunity such as lymphopenia (5), impaired Ab response to immunization (6,7), as well as decreased levels of IgA (8). Deficits in innate immunity have also been identified primarily involving impaired neutrophil chemotaxis (9,10).…”
mentioning
confidence: 99%